2016
DOI: 10.1002/nur.21769
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Internet in Care Initiation by People Living With HIV

Abstract: Over the past 20 years, people increasingly use the Internet to obtain information, including information about health. Yet, we lack understanding of how people living with HIV (PLHIV) use the Internet in their care and treatment decisions. Interviews with 23 individuals who initiated HIV care at an urban, Midwestern medical center were analyzed to explore how they used the Internet during the process of initiating HIV care. The time frame of initiation of HIV care ranged from less than one month to a delay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…The issue of low adherence (Sianturi, Perwitasari, Islam, & Taxis, 2019) The latest report shows that over 93% of Indonesians were literate (Indonesia S, 2013), and internet users (Asosiasi Penyelenggara Jasa Internet Indonesia, 2017). Studies have shown that PLHIV use the internet to obtain information to make health decisions (Perazzo, Haas, Webel, & Voss, 2017) and as support to deal with depressive symptoms of being infected with HIV (van Luenen, Garnefski, Spinhoven, & Kraaij, 2018). Previous studies showed that health literacy was associated with sociodemographic variables such as gender, age, level of education, and race (Waite, Paasche-Orlow, Rintamaki, Davis, & Wolf, 2008).…”
mentioning
confidence: 99%
“…The issue of low adherence (Sianturi, Perwitasari, Islam, & Taxis, 2019) The latest report shows that over 93% of Indonesians were literate (Indonesia S, 2013), and internet users (Asosiasi Penyelenggara Jasa Internet Indonesia, 2017). Studies have shown that PLHIV use the internet to obtain information to make health decisions (Perazzo, Haas, Webel, & Voss, 2017) and as support to deal with depressive symptoms of being infected with HIV (van Luenen, Garnefski, Spinhoven, & Kraaij, 2018). Previous studies showed that health literacy was associated with sociodemographic variables such as gender, age, level of education, and race (Waite, Paasche-Orlow, Rintamaki, Davis, & Wolf, 2008).…”
mentioning
confidence: 99%
“…Os jovens se mostram curiosos com relação ao seu tratamento e, desse modo, eles se ocupam, buscam informações, explicações e conselhos com relação à TARV, informando-se sobre o mesmo. Uma das possibilidades de busca por informações é o uso da internet, a qual tem o potencial de formar opiniões, auxiliando nas decisões acerca do tratamento das pessoas vivendo com HIV (30).…”
Section: Discussionunclassified
“…The mixed emotional response reported by the majority of our sample of PLWH at the time of diagnosis is supported by theory demonstrating the coincidence of positive and negative emotions during crises (Folkman & Moskowitz, 2000) yet contrasts with some of the findings of previous qualitative studies. Qualitative literature on HIV is saturated with narratives of PLWH describing the trauma of HIV-diagnosis (Perazzo, 2015; Psaros et al, 2015). Fear, dread, shame, and guilt are emotions often recalled by PLWH when asked to describe their feelings around this pivotal event in their lives (Perazzo, 2015; Psaros et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative literature on HIV is saturated with narratives of PLWH describing the trauma of HIV-diagnosis (Perazzo, 2015; Psaros et al, 2015). Fear, dread, shame, and guilt are emotions often recalled by PLWH when asked to describe their feelings around this pivotal event in their lives (Perazzo, 2015; Psaros et al, 2015). Although a negative reaction to receiving this sort of news is expected and was also found among most participants in the present study, we found that other people can experience a range of emotions with varying intensity.…”
Section: Discussionmentioning
confidence: 99%